Controllable self-assembly of NaREF4 upconversion nanoparticles and their distinctive fluorescence properties. (13th June 2016) - Liu, Xiaoxia; Ni, Yaru; Zhu, Cheng; Fang, Liang; Kou, Jiahui; Lu, Chunhua; Xu, Zhongzi
Abstract: The paper presents the growth of hexagonal NaYF4 :Yb 3+, Tm 3+ nanocrystals with tunable sizes induced by different contents of doped Yb 3+ ions (10%–99.5%) using the thermal decomposition method. These nanoparticles, which have different sizes, are then self-assembled at the interface of cyclohexane and ethylene and transferred onto a normal glass slide. It is found that the size of nanoparticles directs their self-assembly. Due to the appropriate size of 40.5 nm, 15% Yb 3+ ions doped nanoparticles are able to be self-assembled into an ordered inorganic monolayer membrane with a large area of about 10 × 10 μ m 2 . More importantly, the obvious short-wave (300–500 nm) fluorescence improvement of the ordered 2D self-assembly structure is observed to be relative to disordered nanoparticles, which is because intrinsic absorption and scattering of upconversion nanoparticles leads to the self-loss of fluorescence, especially the short-wave fluorescence inside the disordered structure, and the relative emission of short-wave fluorescence is reduced. The construction of a 2D self-assembly structure can effectively avoid this and improve the radiated short-wave fluorescence, especially UV photons, and is able to direct the design of new types of solid-state optical materials in many fields.